Epistemology and metaphysics for qualitative research - Pernecky, Tomas (Sage Publications, 2016)
This clearly written and provocative text outlines the wide range of epistemological and metaphysical pillars of research. In a clear, easy to follow style, the reader is guided through an array of concepts that are defined, explained and made simple. With the aid of helpful examples and case studies, the book challenges the prevailing modes of thinking about qualitative inquiry by showcasing an immense variety of philosophical frameworks. Armed with a strong understanding of this philosophical backbone, students will be able to choose and defend a 'pick and mix' of research methods that will uniquely complement their research. Empiricism, Rationalismk, Realism, Skepticism, Idealism, Positivism, Post-positivism, Idea-ism, Hermeneutics, Phenomenology, Social Ontology, Quantum Mechanics Essential reading for new and experienced researchers, this 'must' for any social science bookshelf will help unlock a new level of research creativity.